How successful people grow 15 ways to get ahead in life - Maxwell, John C. 1947- (Center Street, 2014)
Are there tried and true principles that are always certain to help a person grow? John Maxwell says the answer is yes. He has been passionate about personal development for over fifty years, and here, he teaches everything he has gleaned about what it takes to reach our potential. In the way that only he can communicate, John teaches ... The Law of the Mirror: You Must See Value in Yourself to Add Value to YourselfThe Law of Awareness: You Must Know Yourself to Grow YourselfThe Law of Modeling: It's Hard to Improve When You Have No One But Yourself to FollowThe Law of the Rubber Band: Growth Stops When You Lose the Tension Between Where You are and Where You Could BeThe Law of Contribution: Developing Yourself Enables You to Develop Others This compact read will help readers become lifelong learners whose potential keeps increasing and never gets "used up